Parental perceptions of family adjustment in childhood developmental disabilities. (March 2013) - Thompson, Sandra; Hiebert-Murphy, Diane; Trute, Barry
Based on the adjustment phase of the double ABC-X model of family stress (McCubbin and Patterson, 1983) this study examined the impact of parenting stress, positive appraisal of the impact of child disability on the family, and parental self-esteem on parental perceptions of family adjustment in families of children with disabilities. For mothers, self-esteem and positive appraisal predicted maternal-perceived family adjustment and mediated the relationship between parenting stress and family adjustment. For fathers, while self-esteem and positive appraisal were not significant in directly predicting perceived family adjustment, self-esteem moderated the relationship between parenting stress and family adjustment. These results suggest that interventions that bolster self-esteem in parents may be useful in enhancing perceptions of family adjustment. Similarly, interventions that enhance mothers' experiences of the positive aspects of parenting a child with disabilities hold potential to strengthen family adjustment.